ANALISIS STRATEGI DIGITAL MARKETING PADA PERUSAHAAN PIALANG BERJANGKA PT MIDTOU ARYACOM FUTURES DI MASA PANDEMI COVID-19 - Syahidah Sapira (2022)
Technological advances are increasingly rapid, resulting in rapid communication and encouraging integration in financial markets. Business activities are experiencing a new phase, due to the Covid-19 pandemic, one of which is activities in marketing products. From the Covid-19 pandemic, the use of social media with various platforms has increased, this is due to changes in marketing activities that are usually carried out offline and have to switch to online. From the public's tendency to use social media as a communication channel to obtain various information during the covid-19 pandemic, this has also become a challenge for companies to do marketing through digital media to still be able to reach the wider community even during this covid-19 pandemic. This has encouraged various companies, including the financial sector, one of which is a futures brokerage company that uses digital marketing methods. The purpose of this research is to find out the digital marketing strategy of the futures brokerage company PT Midtou Aryacom Futures. The research method used is a qualitative case study approach. Data obtained through interviews, direct observation and documentation. Data analysis was performed using Microsoft Excel. The results of the analysis using the seven stages of e-marketing planning can be categorized as quite effective.